Digital Twin-Based Real-Time Monitoring System for Safety of Multiple Laptops in Working Environment - Minh Long Hoang; Nicola Delmonte (IEEE Open Journal of Instrumentation and Measurement)
Overheating is a significant issue for laptops, especially in working environments where multiple laptops are utilized to launch heavy programs without the user’s presence frequently. The proposed monitoring method is based on a digital twin (DT) system in a workstation that monitors the heat power loss of the battery, relying on the measurements of the battery current, the central processing units (CPUs) temperatures, and graphics processing units (GPUs) temperatures. Other personal computer (PC) laptops deliver their data via transmission control protocol (TCP)/Internet protocol (IP). The workstation sends a query message, allowing each PC to transfer the necessary information. The virtual system handles the received data to proceed with the alert system for warning if these parameters overcome the concerned threshold. The DT system is implemented into a Dell workstation based on MATLAB-Simulink to manage the data from ten other PCs in the experiment. Power loss is calculated in the DT Simulink system based on the electrical circuit of the PC in plugged-in mode and discharge mode. Together with other factors, the system successfully monitors and detects the current situation with a specific alert function. The monitored parameters can be observed for each setting-up period, which allows the manager to comprehend the condition state during a specific time.